Numerical and experimental studies of a Capillary-Tube embedded PCM component for improving indoor thermal environment - Mohamad Iskandar, Jobli; Runming, Yao; Zhiwen, Luo; Shahrestani, Mehdi; Nan, Li; Hong, Liu (Elsevier, 2019)
This paper aims to analyse the thermal characteristics of a novel system of Capillary Tubes embedded in a Phase Change Material (CT-PCM) as part of active building environmental design for energy conservation and the improvement of indoor thermal environment. The CT-PCM system is proposed based on the concept that lowgrade energy utilisation potential could be harnessed and maximised by buildings’ radiant heating/cooling systems and phase change material. The CT-PCM component is first built in the laboratory, and the thermal characteristics of the CT-PCM are investigated through a set of thermal response experiments. In addition, a simplified model is developed to assess the long-term thermal performance of the CT-PCM system for its application during a strategical system design stage. To ensure the robustness of the numerical model in the assessment of the thermal performance of the system, the developed model is evaluated against the experiments under a set of dynamic thermal boundary conditions. The evaluation process revealed that when the flow rate of thermal fluids in the CT-PCM system is more than 800 ml/min, the simulation results of the proposed simplified model is in a good agreement with the experiment. When the flow rate in the capillary tube is smaller than 800 ml/min, the correction factors are derived to address the non-uniformity of temperature distribution.